Changes in dietary fiber fractions and gut microbial fermentation properties of wheat bran after extrusion and bread making. (August 2015) - Arcila, Jennifer A.; Weier, Steven A.; Rose, Devin J.
Abstract: The dietary fiber in wheat bran, principally non-starch polysaccharides (NSP), is mostly water-unextractable and is poorly utilized by human gut microbiota. The purpose of this study was to determine the change in water-extractability of NSP in wheat bran upon extrusion and then to determine if extrusion impacts the availability of NSP for fermentation by the fecal microbiota during in vitro fecal fermentation. A secondary objective was to incorporate extruded bran into a product formulation to determine if changes in WE-NSP and NSP fermentation were maintained in a finished product. Bran was extruded using combinations of high or low moisture (15% and 30% wb) and high or low screw speed (120 and 250 rpm). All extrusion conditions resulted in increases in WE-NSP and fecal microbiota short chain fatty acid (SCFA) production upon fermentation compared with unextruded bran. Low screw speed and low moisture resulted in the greatest increase in WE-NSP (3-fold) as well as the highest production of SCFA during fermentation (1.4-fold) compared with unextruded bran. Whole wheat breads containing extruded bran did not show increases in either WE-NSP or SCFA production compared with the control. In conclusion, extrusion of wheat bran increased WE-NSP, which enabled greater fermentability by human fecal microbiota. However, once extruded bran was used in a whole wheat bread formulation the changes in fermentation outcomes were no longer evident. Highlights: Extrusion resulted in increased water-extractable non-starch polysaccharide extractability in wheat bran. Extrusion resulted in increased non-starch polysaccharide fermentation in short chain fatty acids during fermentation. Extrusion increases short chain fatty acid production during fermentation. These effects were no longer clearly evident when extruded bran was incorporated into bread.